PENGARUH HUTANG, UKURAN PERUSAHAAN DAN MODAL SENDIRI TERHADAP PROFITABILITAS PERUSAHAAN PERHOTELAN DI INDONESIA DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING. - Winny Hosea; Kohar Sulistyadi; Heri Ispriyahadi (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2017)
This study aims to identity the impact of fnancial leverage, corporate size and capital on the proftability of hotel’s company in Indonesia. The Study used capital structure as an intervening variable. On this Study, the researcher selected the fnancial data from 10 Hotel’s Company which is listed in Indonesian Stock Exchange. The period of research are 10 years from 2007 untill 2016. Based on the fnancial data provided, the researcher has 100 obeservation data. The Study used path anlysis with the out put result as an beta of the impact and path diagram, the beta will be add on the path equation and this study will translate and intepretation the path equation. The result of the study are there is signifcant impact between fnancial leverage and Capital Structure, Capital has a negative impact to the Capital Structure, Financial Leverage has negative impact to the proftability, Corporate Size has signifcant impact to the Proftability, Capital has negative impact to the Proftability and Capital Structure has negative impact to Proftability of Hotel’s Company in Indonesia. Based on the result of the study above, can be concluded the management of source of fund which consist of external source of fund (Financial Leverage) and internal source of fund (Capital) not good enough managed by the company that made the uses of the source of fund has decrease the proftability of Hotel’s Company in Indonesia.